Evaluation Of The Spatial Distribution Of Public Health Services in The City Of Bani Walid using Geography information Systems (Journal of Libya for geographical studies, 2023)
This study aims to evaluate the health services in the city of Bani Walid, where knowledge of the spatial distribution of health services is important to know the extent of efficiency and suitability of the spatial distribution of health services with the population, depending on the available data. The available numbers of data on the number of hospitals and primary health care centers have been compared. Comparing it with its counterparts according to international and local standards. In this research, geographic information systems (GIS) techniques were used, such as quantitative methods, to highlight their capabilities in analyzing spatial distribution (using the standard distance, the proximity correlation coefficient, the actual rate center, and the average geographical center to identify the scope of health service and the efficiency of accessibility to service) in order to find spatial relationships between health services and produce their results on Form spatial maps after analyzing the metadata. Which led to inconsistency in their distribution, and the study concluded that the services are distributed irregularly in a distribution pattern (spaced / regular), and a map was produced showing the distribution of health services within the city.
Keywords: Hospital; Health care unit; Spatial analysis; Public health services